The parallel universes of David Shrayer-Petrov : a collection published on the occasion of the writer's 85th birthday - Shraer-Petrov, David; Katsman, Roman; Shrayer, Maxim, 1967-; Smola, Klavdii͡a (Jews of Russia & Eastern Europe and their legacy., 2021)
"This volume celebrates the literary oeuvres of David Shrayer-Petrov-poet, fiction writer, memoirist, essayist, and literary translator (and medical doctor and researcher in his parallel career). Author of the refusenik novel Doctor Levitin, Shrayer-Petrov is one of the most important representatives of Jewish-Russian literature. Published in the year of Shrayer-Petrov's eighty-fifth birthday, thirty-five years after the writer's emigration from the former USSR, this is the first volume to gather materials and investigations that examine his writings from various literary-historical and theoretical perspectives. By focusing on many different aspects of Shrayer-Petrov's multifaceted and eventful literary career, the volume brings together some of the leading American, European, Israeli and Russian scholars of Jewish poetics, exilic literature, and Russian and Soviet culture and history. In addition to fifteen essays and an extensive interview with Shrayer-Petrov, the volume features a detailed bibliography and a pictorial biography"--